Economic impact of dyspepsia in rural and urban Malaysia: a population-based study - Mahadeva, S.; Yadav, H.; Everett, S.M.; Goh, K.L. (Korean Society of Neurogastroenterology and Motility, 2012)
Background/Aims : The economic impact of dyspepsia in regions with a diverse healthcare system remains uncertain. This study aimed to estimate the costs of dyspepsia in a rural and urban population in Malaysia.Methods Economic evaluation was performed based on the cost-of-illness method. Resource utilization and quality of lifedata over a specific time frame, were collected to determine direct, indirect and intangible costs related to dyspepsia. Results The prevalences of dyspepsia in the rural (n = 2,000) and urban (n = 2,039) populations were 14.6% and 24.3% respectively. Differences in socioeconomic status and healthcare utilisation between both populations were considerable. The cost of dyspepsia per 1,000 population per year was estimated at USD14,816.10 and USD59,282.20 in the rural and urban populations respectively. The cost per quality adjusted life year for dyspepsia in rural and urban adults was USD16.30 and USD69.75, respectively.Conclusions The economic impact of dyspepsia is greater in an urban compared to a rural setting. Differences in socioeconomic status and healthcare utilisation between populations are thought to contribute to this difference.